Comparision of antimicrobial alternatives in irradiated diets for nursery pigs - Keegan, T.P.; Hasted, C.W.; DeRouchey, Joel M.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Previous research at Kansas State University indicated that irradiation can effectively reduce the bacteria concentration in nursery diets. Therefore, we hypothesized that eliminating bacteria in the feed via irradiation would provide a model to determine the effectiveness of antimicrobial alternatives. In a 27-d growth assay, 330 weanling pigs (13.2 lb and 18 ± 2 d of age, PIC) were fed one of 9 experimental diets: 1) control diet with no antimicrobials, 2) irradiated control diet with no antimicrobials, and the irradiated control diet with added: 3) carbadox (50 g/ton), 4) Probios® (1.6% from d 0 to 14 and 0.8% from d 14 to 21), 5) BioSaf® (0.3%), 6) Biomate Yeast Plus® (0.1%), 7) Bio-Mos™ (0.3%), 8) Bio-Plus® 2B (0.05%), or 9) LactoSacc® (0.2%). BioSaf®, Biomate Yeast Plus®, and Lacto Sacc® are all concentrated forms of selected live yeast cells while Bio-Mos™ is a mannanoligosaccharide derived from yeast. Probios® is a form of lactic acid bacteria and Bio Plus® 2B contains two bacillus strains. All antimicrobials were added after diets were irradiated. Neither irradiation nor feed additives in an irradiated diet improved growth performance compared to the nonirradiated control. Pigs fed the diet containing Probios had poorer (P<0.05) F/G compared to all other test diets except pigs fed the diet containing BioSaf. Pigs fed both the non-irradiated and irradiated control diets and Bio Plus 2B had improved (P<0.05) F/G compared to pigs fed diets containing Probios and BioSaf. These results indicate that whole diet irradiation or adding the feed additives to the irradiated diet did not improve growth performance. Eliminating the bacteria in the control diet by irradiation did not allow the impact of antimicrobial alternatives to be more easily measured.
Keywords: Nursery pig; Irradiation; Feed additive; Swine